Transforming Growth Factor Beta-Activated Kinase 1–Dependent Microglial and Macrophage Responses Aggravate Long-Term Outcomes After Ischemic Stroke. Issue 3 (March 2020) - Wang, Rongrong; Pu, Hongjian; Ye, Qing; Jiang, Ming; Chen, Jie; Zhao, Jingyan; Li, Sicheng; Liu, Yaan; Hu, Xiaoming; Rocha, Marcelo; Jadhav, Ashutosh P.; Chen, Jun; et al.
Abstract : Background and Purpose—: Microglia/macrophages (Mi/MΦ) can profoundly influence stroke outcomes by acquiring functionally dominant phenotypes (proinflammatory or anti-inflammatory; deleterious or salutary). Identification of the molecular mechanisms that dictate the functional status of Mi/MΦ after brain ischemia/reperfusion may reveal novel therapeutic targets for stroke. We hypothesized that activation of TAK1 (transforming growth factor beta-activated kinase 1), a key MAP3K upstream of multiple inflammation-regulating pathways, drives Mi/MΦ toward a proinflammatory phenotype and potentiates ischemia/reperfusion brain injury. Methods—: Young adult mice were subjected to 1 hour of middle cerebral artery occlusion (MCAO) followed by reperfusion. TAK1 was targeted by tamoxifen-induced Mi/MΦ-specific knockout or administration of a selective inhibitor 5Z-7-Oxozeaenol after MCAO. Neurobehavioral deficits and long-term gray matter and white matter injury were assessed up to 35 days after MCAO. Mi/MΦ functional status and brain inflammatory profiles were assessed 3 days after MCAO by RNA-seq, flow cytometry, and immunohistochemistry. Results—: TAK1 Mi/MΦ-specific knockout markedly ameliorated neurological deficits in the rotarod and cylinder tests for at least 35 days after MCAO. Mechanistically, RNA-seq of purified brain Mi/MΦ demonstrated that proinflammatory genes and their predicted biological functions were downregulated or inhibited in microglia and macrophages from TAK1 Mi/MΦ-specific knockout mice versus WT mice 3 days after MCAO. Consistent with the anti-inflammatory phenotype of Mi/MΦ-specific knockout, oxozeaenol treatment mitigated neuroinflammation 3 days after MCAO, manifested by less Iba1 + /CD16 + proinflammatory Mi/MΦ and suppressed brain invasion of various peripheral immune cells. Oxozeaenol treatment beginning 2 hours after MCAO improved long-term sensorimotor and cognitive functions in the foot fault, rotarod, and water maze tests. Furthermore, Oxozeaenol promoted both gray matter and white matter integrity 35 days after MCAO. Conclusions—: TAK1 promotes ischemia/reperfusion-induced inflammation, brain injury, and maladaptive behavior by enhancing proinflammatory and deleterious Mi/MΦ responses. Therefore, TAK1 inhibition is a promising therapy to improve long-term stroke outcomes. Abstract : Supplemental Digital Content is available in the text.